Medical Management of Fecal Incontinence in Challenging Populations: A Review - Lee, David; Arora, Gaurav (Clinics in Colon and Rectal Surgery, 2014)
Fecal incontinence (FI) is a common and growing problem in the United States. Although there are multiple emerging novel interventions for the treatment of FI, the mainstay of initial therapy remains medical management. In this article, we review the available literature on the medical management of FI, with a special focus on patients with multiple sclerosis, diabetes mellitus, and the elderly.
Keywords: fecal incontinence; anorectal dysfunction; multiple sclerosis; diabetes mellitus; elderly